A prospective study to analyze the etiology, prevalence, clinical presentation, age and sex wise distribution of thyrotoxicosis among thyroid disorders in a tertiary care hospital - Nirmalanandan, Manoj Kumar; Balachandran, Kavitha Jayanthi (International Surgery Journal, 2020)
Background: Thyrotoxicosis is a clinical syndrome characterized by an excess of free thyroxine and triiodothyronine or both. One of the major and usual causes of thyrotoxicosis is Graves’ disease. Morbidity associated with the situation is very high and it demands early diagnosis and treatment. This can reduce the burden of the disease it imparts on the society. The aim of the study is to analyse the etiology, prevalence, clinical presentation, age, and sex-wise distribution of thyrotoxicosis among thyroid disorders presenting to Government Medical College, Thiruvananthapuram. Methods: It is a prospective study undertaken in tertiary care and teaching hospital over a period of one year. 2401 patients admitted in the general ward with thyroid disorders were included in the study. Definite inclusion and exclusion criteria were followed. Relevant blood tests were done in all cases. Results: On analysis of the data which were entered in excel format the prevalence of thyrotoxicosis was 2.5%. The majority of the study population was in the twenties and forties. Incidences in females were more mainly due to increased prevalence. Conclusions: By studying the etiology, prevalence, clinical presentation, age, and sex-wise distribution of Thyrotoxicosis, the disease burden in the population can be understood and early diagnosis and proper treatment can be instituted. Our study prevalence was comparable with similar studies done in other institutions.